2016
DOI: 10.18632/oncotarget.9593
|View full text |Cite
|
Sign up to set email alerts
|

Dietary phytochemicals and cancer chemoprevention: a review of the clinical evidence

Abstract: Cancer chemoprevention involves the use of different natural or biologic agents to inhibit or reverse tumor growth. Epidemiological and pre-clinical data suggest that various natural phytochemicals and dietary compounds possess chemopreventive properties, and in-vitro and animal studies support that these compounds may modulate signaling pathways involved in cell proliferation and apoptosis in transformed cells, enhance the host immune system and sensitize malignant cells to cytotoxic agents. Despite promising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
240
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(249 citation statements)
references
References 126 publications
(135 reference statements)
0
240
0
9
Order By: Relevance
“…However, the overall treatment efficiency for malignant and metastatic breast cancer remains stagnant. Recent studies have identified effective phytochemicals for the treatment of cancer, including advanced stage breast cancer (26)(27)(28). Therefore, the potential of morusin as a therapeutic agent for breast cancer was evaluated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the overall treatment efficiency for malignant and metastatic breast cancer remains stagnant. Recent studies have identified effective phytochemicals for the treatment of cancer, including advanced stage breast cancer (26)(27)(28). Therefore, the potential of morusin as a therapeutic agent for breast cancer was evaluated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Chemoprevention is the administration of natural products or synthetic compounds to inhibit tumorigenesis, trigger apoptosis, or both, in tumor cells (1). However, natural chemopreventive agents, which include polyphenols, alkaloids, carotenoids, and nitrogen compounds, have little or no toxicity in normal cells (1).…”
Section: Introductionmentioning
confidence: 99%
“…However, natural chemopreventive agents, which include polyphenols, alkaloids, carotenoids, and nitrogen compounds, have little or no toxicity in normal cells (1). Flavonoids are compounds isolated from a wide range of dietary foods, including vegetables, fruit, wine and tea, and have received a attention due to their chemopreventive and chemotherapeutic activities (2).…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical agents constitute a heterogeneous set of bioactive compounds including alkaloids, polyphenols, carotenoids, and nitrogen compounds. These compounds are naturally found in vegetables, fruits, grains and other plant products and are generally responsible for several plant features such as: smell and color pigmentation (1). For a long time, the medicinal plants have been traditionally used to treat human disorders (2) and about 70 % of antitumoral drugs are natural products or their derivatives (3,4).…”
Section: Introductionmentioning
confidence: 99%